A remarkable annealing time effect on the magnetic properties of single-source coordination polymer precursor-derived CoFe2O4 nanoparticles. (21st November 2019) - Ghosh, Debamalya; Singha, Debal Kanti; Lebedev, Oleg I.; Seikh, Md. Motin; Mahata, Partha
Abstract : The diversity in the magnetocrystalline anisotropy of nano-sized CoFe2 O4 samples has been derived from coordination polymers through differential occupancy of Co 2+ in octahedral sites. Abstract : A bimetallic coordination polymer (CP) {(H2 pip)[Co1/3 Fe2/3 (pydc-2, 5)2 (H2 O)]·2H2 O} {where H2 pip = piperazinediium, pydc-2, 5 = pyridine-2, 5-dicarboxylate}, 1, was successfully synthesized using the hydrothermal technique. To establish the structure and confirm the phase purity of 1, the PXRD pattern of the synthesized compound was compared with the simulated PXRD pattern generated from the single-crystal X-ray data of an isomorphous pure Fe compound synthesized earlier by us. Systematic characterizations of compound 1 were performed by IR, TGA, SEM and EDX elemental mapping analysis. Compound 1 was used as a single-source precursor for the preparation of nano-sized CoFe2 O4 with different sizes via thermal decomposition under different conditions. The precursor annealed at 300 °C resulted in an amorphous sample and a crystalline phase was achieved at 325 °C. The temperature of 325 °C was attained at the rate of ∼5 °C min −1 and maintained for 30 min to obtain sample 2, and the furnace was switched off within 2 min after the temperature was attained to obtain sample 3 . The amorphous phase was labelled as sample 4 . The as-obtained CoFe2 O4 nanoparticles were characterized by PXRD, SEM, TEM and EDX elemental mapping analysis. The particle sizes were 11 nm and 13 nm for the samples treated for 2 min and 30 min, respectively. The differential thermal treatment by half an hour resulted in a dramatic change in the magnetic properties of cobalt ferrite. Sample 2 exhibited four-fold larger magnetization at room temperature than sample 3 even though they had comparable particle sizes. This result can be ascribed to the preferential occupancy of Co 2+ in octahedral sites with an increase in annealing time, which eventually produces large magnetocrystalline anisotropy.